Targeting of proteins to the Golgi apparatus - Gleeson, Paul A. (Glycoconj J, 1994)
The Golgi apparatus maintains a highly organized structure in spite of the intense membrane traffic which flows into and out of this organelle. Resident Golgi proteins must have localization signals to ensure that they are targeted to the correct Golgi compartment and not swept further along the secretory pathway. There are a number of distinct groups of Golgi membrane proteins, including glycosyltransferases, recyclingtrans-Golgi network proteins, peripheral membrane proteins, receptors and viral glycoproteins. Recent studies indicate that there are a number of different Golgi localization signals and mechanisms for retaining proteins to the Golgi apparatus. This review focuses on the current knowledge in this field.